Spatial and socioeconomic inequalities in the access to safe drinking water in Peruvian households - Ali Al-; Claudia Silva-Perez; Pamela Robles-Valcarcel; Guido Bendezu-Quispe; Amado Insfrán Ortiz; Vicente A. Benites-Zapata (IWA Publishing, 2023)
Access to safe drinking water has increased in Peru over the last decades, from 47% (2008) to 52% (2018). Nevertheless, such access would differ according to socioeconomic and regional factors. Thus, this study aimed to assess the socioeconomic inequality in the access to safe drinking water and identify its spatial distribution. We conducted a cross-sectional study based on the secondary data analysis of the 2021 Peruvian Demographic and Health Survey. Access to safe drinking water was a dummy variable categorised as safe if the residual chlorine concentration was ≥0.5 mg/L. Nationwide, 29.22% of households had access to safe drinking water. A pro-rich inequality in access to safe drinking water was observed. The spatial distribution was clustered. Significant hotspots were found in the south and centre of the country; however, cold spots were found in most areas. SaTScan analysis identified 32 and 63 significant clusters at high and low risks of having access to safe drinking water, respectively. In conclusion, approximately one out of four Peruvian households has access to safe drinking water, which was mostly concentrated among the wealthier households. Intra- and interdepartmental inequalities in access to safe drinking water were found, with several high-risk clusters. HIGHLIGHTS Major socioeconomic and spatial inequalities in the access to safe drinking water were identified.; The socioeconomic distribution of access to safe drinking water was greatly pro-rich in all departments.; Nearly half of the richest population and <5% of the poorest population had access to safe water.; Intra- and interdepartmental inequalities in the access to safe drinking water were found.;